(untitled) (International Journal of Biomedical Research, 2020)
Aim: To study the spectrum and frequency of various renal diseases; profile of various renal disease in different age groups was also studied. Material and method: Ultrasound assisted percutaneous renal biopsy with routine H&E staining was done. Periodic acid schiff, Masson Trichome, Silver Methinamine and Congo red done where needed. Result: Renal biopsies from total of 100 patients suspected with renal disease were evaluated. Maximum incidence of renal disease was seen in the age group 41-50 years which comprised 24% of total cases. 56 patients (56%) were male and 44 (44%) patients were female. Most of the benign diseases were seen in age group 41-50 Yrs and malignant diseases were seen in 61-70 yrs of age. Minimal change disease was commonest cause of nephrotic syndrome. The commonest cause of chronic kidney disease/chronic renal failure was chronic glomerulonephritis and for acute renal failure were toxins. Acute tubular necrosis was commonest histopathological finding seen in acute renal failure Minimal change disease was commonest cause of nephrotic syndrome. Commonest histopathological feature in nephritic syndrome was tubulointerstitial nephritis Conclusion: Early diagnosis of kidney diseases with renal biopsy lead to appropriate treatment and prevented the end stage renal disease.